Comparison of lactose, Sodium Lauryl Sulphate (SLS) & Pluonic in dissolution profile of Ibuprofen prepared by crystallization method - Mow, Farhana Afrin (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2020.